Hepatitis A outbreak among men who have sex with men, Shinjuku, Japan, 2018 - Itaki, Mariya; Endo, Masayuki; Asakura, Hiroyuki; Nagashima, Mami; Somura, Yoshiko; Takahashi, Aki; Kayebeta, Aya; Takahashi, Ikumi; Yahata, Yuichiro (Western Pacific Surveillance and Response, 2025)
Objective: In 2018, the Shinjuku City Department of Health detected excess cases of hepatitis A virus (HAV) infection. The objectives of this investigation were to characterize the outbreak, identify transmission routes among inpatient cases and make recommendations to control and prevent HAV infection among men who have sex with men.Methods: Information about cases of HAV infection was collected from the National Epidemiological Surveillance for Infectious Diseases system and inpatient interviews conducted by public health nurses in 2018.Results: There were 131 HAV cases in 2018. Of these, 98% (129/131) were male, of whom 81% (105/129) were men who have sex with men. Hospitalization was required for 40 cases (31%). The age groups with the highest proportion of cases were 30–39 and 40–49 years (each 34%; 44/131). Two cases (2%) had received the second dose of the HAV vaccine, but only 10 days before symptom onset; all others had received no doses. The sequence type subgroup 13, an RIVM-HAV-16–090-like strain, was seen in 51 cases (39%). Of the 40 hospitalized cases, 21 (53%) participated in an interview conducted using a semistructured questionnaire. Altogether, of 21 cases, 12 (57%) had coinfection with HIV, 13 (62%) had casual sexual contact within the preceding 2 months and 10 (48%) had used social networking services (SNS) to find a sexual partner.Discussion: In Shinjuku, this outbreak almost exclusively affected the population of men who have sex with men. The detected outbreak strain has previously been reported in outbreaks among men who have sex with men in Taiwan (China) and Europe. For HAV prevention, the most important measures are raising awareness of the risk of HAV as a sexually transmitted infection via SNS and promoting immunization at the appropriate time.
Keywords: hepatitis A; infectious disease outbreaks; sexual and gender minorities; hepatitis A vaccines; sexually transmitted infections; vaccine preventable diseases; Japan